Meta-Analysis Results on the Association Between TP53 Codon 72 Polymorphism With the Susceptibility to Oral Cancer - Lin, Ying-Mei; Shao, Jun; Yin, Xiao-Hong; Huang, CaiCai; Jia, Xiao-Wei; Yuan, Ya-Di; Wu, Chang-Jing; Zhen, En-Ming; Yao, Zhong-Xiong; Zeng, Xian-Tao; Liu, Rui-Hua (Frontiers in Physiology, 2018)
Objectives: TP53 is an important tumor suppressor gene to maintain genomic integrity, and its mutations increase the susceptibility to oral carcinoma. Previous published studies have reported the relation of TP53 codon 72 polymorphism with the risk of oral carcinoma, but the results remain controversial and inconclusive. Methods: We therefore utilized meta-analysis based on a comprehensive search in PubMed, EMBASE, and Google of Scholar databases up to August 19, 2017. Results: Total 3,525 cases and 3,712 controls from 21 case-control studies were selected. We found no significant association between TP53 codon 72 polymorphism and oral carcinoma susceptibility in all genetic contrast models, including subgroup analysis based on control source and ethnicity. Furthermore, TP53 codon 72 polymorphism was not significant associated with oral carcinoma susceptibility in tobacco or alcohol use, and HPV infection status. Our results were confirmed by sensitivity analysis and no publication bias was found. Conclusions: Taken together, our data indicate that TP53 codon 72 polymorphism is not associated with the susceptibility to oral carcinoma.